First-order prudence and its implications for precautionary savings and the risk-free rate - Ebert, Sebastian; Karehnke, Paul (Elsevier, 2023)
Prudence is widely known for inducing precautionary saving behavior. This paper revisits this important implication by introducing the notions of first-order and second-order prudence. Within smooth expected utility (EU), prudence is second-order. In that case, the presence of a small, positive-mean risk to future wealth reduces saving, while first-order prudence can increase them. The latter is the case for non-EU theories such as rank-dependent or reference-dependent utility, and the increased savings help resolve the so-called risk-free rate puzzle. By proposing a novel utility function that features first-order prudence, we show that the risk-free rate puzzle can be resolved even within the EU paradigm.